2012
DOI: 10.1002/ejlt.201100019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold‐pressed and vitamin E‐enriched flaxseed oils on lipid profile and antioxidant status in high‐fat fed rats

Abstract: In this study we evaluate whether cold-pressed flaxseed oil (CFO), vitamin E-enriched hot pressed and totally refined flaxseed oils (HRFOs) characterized by different qualities of micronutrients have beneficial effects on lipid profile and antioxidant status in high-fat fed rats. Male Wistar rats were fed synthetic diets containing 10% of HRFO, CFO, low-dose (100 mg/100 g oil) vitamin E-enriched HRFO (L-HRFO) or high-dose (200 mg/100 g oil) vitamin E-enriched HRFO (H-HRFO), respectively for 4 wk. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
5
6
0
Order By: Relevance
“…The same is true regarding plasma LDL-C in the present experiment (0.75 mmol/l; Figure 2): the results of the similar experiments with the FO-fed rats are between 1.84 mmol/l (Xiao et al 2012) and 0.23 mmol/l (Popovic et al 2011), the value reported by Campioli et al 2012 (0.81 mmol/l) being very similar to our data.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The same is true regarding plasma LDL-C in the present experiment (0.75 mmol/l; Figure 2): the results of the similar experiments with the FO-fed rats are between 1.84 mmol/l (Xiao et al 2012) and 0.23 mmol/l (Popovic et al 2011), the value reported by Campioli et al 2012 (0.81 mmol/l) being very similar to our data.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly to the present study (Figure 2), FO in the rat diet decreased plasma TC also in most of the recent studies (Lu et al 2011;Takahashi 2011;Campioli et al 2012;Ferramosca et al 2012;Xiao et al 2012). However, Yamazaki et al (2011) and Campioli et al (2012) did not find differences in TC between the FO-fed rats and the control rats.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations